The combined use of adaptive eeg biofeedback and hypoxytherapy methods to optimize the functional state of a human (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article presents the results of studies on the combined effects on the human body of adaptive biofeedback methods by EEG and hypoxic therapy, which make it possible to quickly optimize a person’s functional state by triggering adaptive mechanisms during hypoxia and reoxygenation. The combined use of these methods is proposed to optimize the functional state of a person through nonspecific activation of the central nervous system. The purpose of the research was to evaluate the combined use of adaptive biofeedback methods by EEG and hypoxic therapy to optimize the functional state of a person. The analyze EEG parameters a computer electroencephalograph-analyzer EEGA-21/26 “Encephalan-131-03” from Medicom MTD (Russia) was used. For all persons, EEG was simultaneously recorded from 21 leads according to the international 10-20 system. An advanced analysis of the large spectral power of the main brain rhythms and an analysis of functional brain asymmetry were used. The research results showed the presence of a shift in brain rhythms in adaptive biofeedback training based on EEG in 90% of persons towards high frequencies (alpha activity) with a corresponding decrease in the level of theta activity, which indicates effective correction and optimization of the functional state of the central nervous system in persons.